Plasma production by a sequence of relativistic electron bunches in the transit channel of the dielectric structure - Linnik, A.F.; Onishchenko, I.N.; Pristupa, V.I.; Berezina, G.P.; Omelayenko, O.L.; Us, V.S. (Вопросы атомной науки и техники, 2015)
In the concept of plasma-dielectric wakefield accelerator plasma presence in the transit channel of the dielectric structure plays at significant role in increasing the accelerating field and providing bunches focusing. The results of the study of plasma production directly by exciting relativistic electron bunches in the channel, filled with an inert gas of different pressure. Measured temporal evolution of the density of the produced plasma, that is in a good agreement with estimates of ionization due to binary collisions of bunch electrons with neutrals or to beam-plasma discharge in the corresponding ranges of the gas pressure. У концепції плазмово-діелектричного кільватерного прискорювача істотну роль у збільшенні прискорю-ючого поля та забезпеченні фокусування згустків відіграє наявність плазми в прольотному каналі діелектричної структури. Представлено результати дослідження процесів утворення плазми безпосередньо збуджуючими релятивістськими електронними згустками в каналі, заповненому нейтральним газом різного тиску. Виміряна часова еволюція щільності створюваної плазми, що знаходиться в задовільному узгодженні з оцінками іонізації за рахунок парних зіткнень електронів згустків з нейтралами або розвитку пучково-плазмового розряду у відповідних областях тиску газу. В концепции плазменно-диэлектрического кильватерного ускорителя существенную роль в увеличении ускоряющего поля и обеспечении фокусировки сгустков играет наличие плазмы в пролетном канале диэлектрической структуры. Представлены результаты исследования процессов образования плазмы непосредственно возбуждающими релятивистскими электронными сгустками в канале, заполненном нейтральным газом различного давления. Измерена временная эволюция плотности возникающей плазмы, находящейся в удовлетворительном согласии с оценками ионизации за счет соударений электронов сгустков с нейтралами или развития пучково-плазменного разряда в соответствующих областях давления газа.